(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Sweet flag (Acorus calamus) is a well-known plant all over the world due to its specific bioactive components β- asarone in plants.The present study reports the quantitative estimation of rhizome oil of the sweet flag plant; obtain from the various district ofUttarakhand, and different geographical surroundings. GC-MS is used to estimate the quantity of rhizome oil. Although leaves areenriched by the several medicinal constituents revealed by the previous studies, rhizome, and the oil it is being investigated. The maincomponent which was identified was Cis-ocimene, Linalool, Trans methyl isoeugenol, β and α-asarone, and euasarone. β-asarone inthe different samples; showed a higher percentage as compared to another component. It was observed that the Gopeshwar regionsample had the 74.36 least percentage and the Pauri sample had the 92.22 highest percentage of β-Asarone. Meanwhile, the Gopeshwarregion sample had 17.25 highest percentage, and the Pauri sample had 1.57 least percentage of α-Asarone. Fungal infection is prevalentnowadays. The oil from all regions subjected to antifungal activity against the Aspirigilla fumigates, A. Parasiticus, MicrosporumCanis, M. gypsum, Cladosporium, Aspergillus niger. The inhibition zone diameter (IZD) against Aspirigilla fumigates, A. parasiticusand was a maximum of 10cm for the Gopeshwar sample,9cm for the Ramnagar sample as compared to the reference drug gentamicin.